Integrative Learning Approach on Learners’ Achievement in Technology and Livelihood Education - THELMA MANABAT (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2020)
The study determined if integrative learning approach could improve learners’ achievement in Technology and Livelihood Education. The respondents of the study were the Grade 10 learners of Muzon Harmony Hills High School during second quarter of school year 2019-2020. Fifty learners participated in the study who were purposively selected and assigned to experimental and control groups. Achievement test and interview guide questions were used. The findings revealed a significant difference between the level of achievement of the experimental and control groups based on the pre-test and post-test. The obtained mean scores of the experimental group in the pre-test was 13.92 and 38.16 in the post-test with the total mean gain of 24.24, while the mean scores of the control group in the pre-test is 13.76 and 28.16 in the post-test with the total mean gain of 14.40. There was a mean difference of 0.16 in the pre-test and 10 in the post-test. After the given intervention, the computed t-value of 6.71 was greater than the obtained critical value of 1.67 and the acquired p-value was less than the alpha level of 0.05. This means that prior to the given intervention there was no significant difference between the achievements of both groups. Hence, after the given intervention, the achievement of learners who were exposed to the integrative learning approach was found significantly better than the achievement of learners who exposed to the conventional approach. Therefore, the hypothesis that there was a significant difference between the achievement of both groups was accepted.